Invisible at birth, congenital melanocytic nevi - Ferrante, MR; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
The clinical and dermoscopic characteristics of 6 nevi which got visible in the first 11 months are reported. Given their size -larger diameter >1.5cm-, these nevi were probably present at birth but invisible. Their progressive darkening from the time of onset and the lack of autonomous growth led us to hypothesize that their invisibility at birth was attributable to the scarce amount of melanic pigment at birth.